2012
DOI: 10.1038/ejhg.2012.248
|View full text |Cite
|
Sign up to set email alerts
|

A focus group study on breast cancer risk presentation: one format does not fit all

Abstract: Identifying a strategy that would optimize both the communication and understanding of the individual breast cancer risk remains a considerable challenge. This study explored the preferences of women with a family history of breast cancer about six presentation formats of individual breast cancer risk, as calculated from a risk prediction model. Thirty-four unaffected women attending genetic counseling because of a family history of breast cancer participated in six focus groups conducted in Qué bec City (2), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…Research on risk communication has demonstrated that preferences for risk formats are likely to vary and there is no consensus on how best to present personalized risk information . Therefore, we included a range of risk formats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on risk communication has demonstrated that preferences for risk formats are likely to vary and there is no consensus on how best to present personalized risk information . Therefore, we included a range of risk formats.…”
Section: Discussionmentioning
confidence: 99%
“…We followed strategies for presenting risk information proposed by Lautenbach et al . and selected different visual representations of disease risk appropriate for a range of numeracy levels and accompanying text that describes the risk in relative and absolute terms. ‘Genetic make‐up’ was described by facilitators at the beginning of the discussion (Appendix S1), and participants were invited to discuss their understanding and to raise any questions regarding risk as presented in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Another key issue to explore is the need for educational support groups (ESGs) in connection with clinical follow-up programs (Dorval et al 2013;Landsbergen et al 2010;Patenaude et al 2008). A Norwegian study by Austvoll-Dahlgren et al (2011) presented positive effect on psychosocial outcomes such as mental health, coping and relationships, and on knowledge regarding own illness, by offering ESG to patients with chronic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Relatedly, Dorval and colleagues highlighted the need for consensus regarding breast cancer risk communication tools given the plethora of breast cancer risk prediction models that provide not easily interpretable probability estimates (78). In their study, participants were shown six different illustrative risk formats, of which they indicated their appreciation of each format.…”
Section: Risk Communicationmentioning
confidence: 99%
“…Appreciation was based on merging of likeability, clarity, perceived risk understanding, and emotional impact. Participants preferred formats that integrated quantitative, qualitative, and visual approaches (78). In general, women at higher risk of breast cancer may view their perceived risk as higher than estimates from cancer risk prediction models; for these women, graphic illustrations may enhance the degree of match (79).…”
Section: Risk Communicationmentioning
confidence: 99%